SISTEM DETEKSI DINI KEBAKARAN BERBASIS IOT UNTUK LINGKUNGAN PENDIDIKAN: STUDI KASUS SMK DIPONEGORO BANYUPUTIH - Setiadi, Teguh; Miftahul Falikhin (Journal of Computer Science and Technology (JCS-TECH), 2025)
Fires can occur unexpectedly, even if you are careful when using equipment that produces fire. However, there are still several sources of fires such as electrical short circuits, gas stoves, burning trash, cigarette butts and candles during a power outage. The purpose of this research is to create a tool that can detect fire and temperature in a room and can overcome (minimize) the threat of fire disasters based on a microcontroller and C language. This research uses a Fire Sensor to detect fire, a DHT 11 Sensor to detect room temperature, NODEMCU as a microcontroller input and output controller, the BLYNK application as a system monitoring tool, a green LED if the room temperature is normal, a yellow LED if the room temperature rises above the normal limit, and a red LED if the room temperature rises drastically. The system will assign the fire extinguishing system using APAR if there is a significant increase in temperature or if the system detects a fire. The output from the Flame Sensor that detects fire will be processed into a microcontroller that has been programmed using C language so that it will produce two states: low when no fire is detected, and high when a fire is detected. Likewise for the output of DHT11. This tool will provide a warning to the BLYNK application if it detects a fire and then gives a command to spray the APAR.